Pengaruh Suhu Dan Kepadatan Ephippia Yang Berbeda Terhadap Penetasan Ephippia Daphnia magna [The Influence Of Defferent Temperature And Ephippia Density For Ephippia Hatch Of Daphnia magna.] - Yudi Cahyoko; Yulian Cindra Eka Pradana; Boedi Setya Rahardja (Jurnal Ilmiah Perikanan dan Kelautan, 2009)
Abstract Daphnia magna has good nutrition to carry on egg produce and fry of fish cupang, maskoki, oscar, tetra, and also can used for food source of fry and seed. Daphnia magna not only supply from natural environment, cause their growth deppend on fertilizer as food and environment condition. The other side: high population density, limited of food source low temperature and shorter irradiation can produce dorman egg (ephippia). The dorman eeg can use for Daphnia magna stock which way by hatching. The factor that can be influence for ephippia hatch are temperature and density. Based on this fact, a research about influence of different temperature and ephippia density for ephippia hatch of Daphnia magna. The purpose of this research was to know the influence of different temperature and ephippia density for ephippia hatch of Daphnia magna. This research has experimental characteristic and use Factorial Completely Randomized Design with three experiments of temperature (A factor), three experiments of density (B factor) and three times replicated. There are 9 kinds of combination between density and temperature. The parameter which checked in this research is degree of hatch of ephippia Daphnia magna and water quality that is dissolve oxygen rate, NH3 and of pH hatch media. The result of the analysis showed that the temperature and density influence of hatching Daphnia magna ephippia. The best result can be used for hatching Daphnia magna ephippia is temperature at 25oC with density 50 ephippia /100 ml giving highest result for the hatch of ephippia Daphnia magna. There are interaction betwen temperature and density for hatching.